Analysis of the trajectory of cognitive function changes and influencing factors in maintenance hemodialysis patients: a prospective longitudinal study - Wenbin Xu; Xiaolian Long; Yuhe Xiang; Aiyin Yu; Ting Luo; Yuhang Chen; Yan Chen; Qian Yang (Renal Failure)
Objectives To explore the trajectory of cognitive function changes and influencing factors in maintenance hemodialysis (MHD) patients.Methods A convenience sampling method was used to select MHD patients from a tertiary hospital in Chengdu from August 2023 to April 2024. The general information questionnaire, Chinese version of the Montreal Cognitive Assessment (MoCA), Pittsburgh Sleep Quality Index (PSQI), Appetite Visual Analogue Scale (VAS), and Family Care Index (APGAR) were used for the investigation. Patients’ cognitive function levels were assessed at baseline and at 3, 6, and 9 months after the initial survey. A latent growth model was used to identify potential categories of cognitive function trajectory, and univariate and binary logistic regression analyses were performed to analyze the influencing factors.Results A total of 154 MHD patients completed the entire study. The trajectory of cognitive function changes was divided into two potential categories: low cognitive function-fast decline group and high cognitive function-slow decline group. Binary logistic regression results showed that educational level, hypertension, sleep quality, appetite, and family care were influencing factors for the trajectory of cognitive function changes in MHD patients.Conclusions Cognitive function in MHD patients showed an overall declining trend over time. The cognitive function change trajectory could be divided into two potential categories: fast decline group and high cognitive function-slow decline group. Healthcare professionals can develop targeted nursing intervention programs based on the characteristics of different patient types and their influencing factors to improve cognitive function and enhance quality of life.